2010
DOI: 10.1038/onc.2010.567
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced intercellular signaling mediated by cytochrome-c via a p53-dependent pathway in hepatoma cells

Abstract: The tumor suppressor p53 has a crucial role in cellular response to DNA damage caused by ionizing radiation, but it is still unclear whether p53 can modulate radiation-induced bystander effects (RIBE). In the present work, three different hepatoma cell lines, namely HepG2 (wild p53), PLC/PRF/5 (mutation p53) and Hep3B (p53 null), were irradiated with γ-rays and then co-cultured with normal Chang liver cell (wild p53) in order to elucidate the mechanisms of RIBE. Results showed that the radiosensitivity of HepG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…In the same experiments we noticed that the level of micronuclei induced in cells co-cultured with non-irradiated ones did not differ between both lines. Recently, He et al (2010) found that the bystander effect after irradiation can be modulated by the p53 status of irradiated hepatoma cells and that a p53-dependent release of cytochrome c may be involved in the RIBE. Following irradiation cytochrome c was released from mitochondria into the cytoplasm only in HepG2 (wild-type p53) cells, but not in PLC/PRF/5 (p53 mutated) or Hep3B (p53-null) cells.…”
Section: The Role Of the P53 Protein In The Response To Bystander Sigmentioning
confidence: 99%
“…In the same experiments we noticed that the level of micronuclei induced in cells co-cultured with non-irradiated ones did not differ between both lines. Recently, He et al (2010) found that the bystander effect after irradiation can be modulated by the p53 status of irradiated hepatoma cells and that a p53-dependent release of cytochrome c may be involved in the RIBE. Following irradiation cytochrome c was released from mitochondria into the cytoplasm only in HepG2 (wild-type p53) cells, but not in PLC/PRF/5 (p53 mutated) or Hep3B (p53-null) cells.…”
Section: The Role Of the P53 Protein In The Response To Bystander Sigmentioning
confidence: 99%
“…Inherent features of the cells may explain their differences in responding to silibinin (i.e., PLC is a HBV-positive and P53 mutated), but HepG2 is a HBV-negative and P53 intact cell [ATCC and (43,44)]. A significant correlation between HBVinfection with both development and recurrence of HCC has been documented (10,45).…”
Section: Discussionmentioning
confidence: 99%
“…Using different combinations of media transfer from p53 wild-type and p53 null HTC116 cells, Mothersill et al (28) showed that both p53 wild-type and p53 null cells are capable of producing signals that induce RIBEs, but that only p53 wild-type cells can respond to signals produced from either cell type. Furthermore, He et al (33) showed that RIBEs can be modulated by the p53 status of irradiated hepatoma cells and that a p53-dependent release of cytochrome-c may be involved in mediating response.…”
Section: Discussionmentioning
confidence: 99%